Unraveling Aspects of Bacillus amyloliquefaciens Mediated Enhanced Production of Rice under Biotic Stress of Rhizoctonia solani - Srivastava, Suchi; Bist, Vidisha; Srivastava, Sonal; Singh, Poonam C.; Trivedi, Prabodh K.; Asif, Mehar H.; Chauhan, Puneet S.; Nautiyal, Chandra S. (Frontiers in Plant Science, 2016)
Rhizoctonia solani (RS) is a necrotrophic fungi causing sheath blight in rice leading to substantial loss in yield. Excessive and persistent use of preventive chemicals raises human health and environment safety concerns. As an alternative, use of biocontrol agents is highly recommended. In the present study an abiotic stress tolerant, plant growth promoting rhizobacteria Bacillus amyloliquefaciens (SN13) is demonstrated to act as a biocontrol agent and enhance immune response against RS in rice by modulating various physiological, metabolic and molecular functions. A sustained tolerance by SN13 primed plant over a longer period of time, post RS infection may be attributed to several unconventional aspects of the plants’ physiological status. The prolonged stress tolerance observed in presence of SN13 is characterized by (a) involvement of bacterial mycolytic enzymes, (b) sustained maintenance of elicitors to keep the immune system induced involving non-metabolizable sugars such as turanose besides the known elicitors, (c) a delicate balance of ROS and ROS scavengers through production of proline, mannitol and arabitol and rare sugars like fructopyranose, β-d glucopyranose and myoinositol and expression of ferric reductases and hypoxia induced proteins, (d) production of metabolites like quinozoline and expression of terpene synthase and (e) hormonal cross talk. As the novel aspect of biological control this study highlights the role of rare sugars, maintenance of hypoxic conditions, and sucrose and starch metabolism in Bacillus amyloliquifaciens (SN13) mediated sustained biotic stress tolerance in rice.